High-energy ball milling and spark plasma sintering of molybdenum - lanthanum oxide (Mo-La2O3) and molybdenum - lanthanum zirconate (Mo-La2Zr2O7) composite powders - Čelko, Ladislav; Tkachenko, Serhii; Casas Luna, Mariano; Dyčková, Lucie; Bednaříková, Vendula; Remešová, Michaela; Komarov, Pavel; Deák, Andréa; Baláž, Matej; Crawford, Deborah E.; Díaz de la Torre, Sebastian; Bodoki, Ede; et al. (Elsevier, 2022)
The current study is focused on the preparation of Mo-10 vol%La2O3 and Mo-10 vol% La2Zr2O7 composite powders via low- and high-energy ball milling approaches as potential candidates for near-future high-temperature structural applications. The mechanical milling parameters play a critical role on the final powder's microstructure. When using the high-energy milling mode (using 800 rpm, ball-to-powder ratio (BPR) 100: 6), the homogeneous powder agglomerates are formed with refined laminated microstructure and more uniform ceramic phase distribution in both Mo-La2O3 and Mo-La2Zr2O7 systems compared to the powders produced by means of the low-energy milling mode (using 350 rpm, BPR 100: 6), where inhomogeneous powder mixture with less embedding of ceramic phases into Mo agglomerates was obtained. This study also focuses on the evaluation of high-temperature phase and microstructural stability of the produced composite powders treated at the temperature of 1300 degrees C under the different gaseous environments, including ambient, inert and reducing atmospheres. The Mo-10 vol% La2Zr2O7 composite powder exhibited better thermal stability during the high-temperature exposure in all tested atmospheres in comparison with the Mo-La2O3 composite powder, since it revealed less intensive formation of the intermediate phases, such as lanthanum oxymolybdates. Therefore, the Mo-10 vol%La2Zr2O7 composite powder was used further for consolidation by means of spark plasma sintering at 1600 degrees C. The successful production of Mo-La2Zr2O7 composite with homogeneous distribution of ceramic phase, the grain size about of 5 mu m, and hardness of 3.4 GPa was not reported so far.

The current study is focused on the preparation of Mo-10 vol%La2O3 and Mo-10 vol% La2Zr2O7 composite powders via low- and high-energy ball milling approaches as potential candidates for near-future high-temperature structural applications. The mechanical milling parameters play a critical role on the final powder's microstructure. When using the high-energy milling mode (using 800 rpm, ball-to-powder ratio (BPR) 100: 6), the homogeneous powder agglomerates are formed with refined laminated microstructure and more uniform ceramic phase distribution in both Mo-La2O3 and Mo-La2Zr2O7 systems compared to the powders produced by means of the low-energy milling mode (using 350 rpm, BPR 100: 6), where inhomogeneous powder mixture with less embedding of ceramic phases into Mo agglomerates was obtained. This study also focuses on the evaluation of high-temperature phase and microstructural stability of the produced composite powders treated at the temperature of 1300 degrees C under the different gaseous environments, including ambient, inert and reducing atmospheres. The Mo-10 vol% La2Zr2O7 composite powder exhibited better thermal stability during the high-temperature exposure in all tested atmospheres in comparison with the Mo-La2O3 composite powder, since it revealed less intensive formation of the intermediate phases, such as lanthanum oxymolybdates. Therefore, the Mo-10 vol%La2Zr2O7 composite powder was used further for consolidation by means of spark plasma sintering at 1600 degrees C. The successful production of Mo-La2Zr2O7 composite with homogeneous distribution of ceramic phase, the grain size about of 5 mu m, and hardness of 3.4 GPa was not reported so far.
High-energy ball milling and spark plasma sintering of molybdenum - lanthanum oxide (Mo-La2O3) and molybdenum - lanthanum zirconate (Mo-La2Zr2O7) composite powders
Keywords: Molybdenum; Lanthanum oxide; Lanthanum zirconium oxide; High-energy milling; Thermal stability; Spark plasma sintering; Molybdenum; Lanthanum oxide; Lanthanum zirconium oxide; High-energy milling; Thermal stability; Spark plasma sintering